Comparison of Oncological and Surgical Outcomes Between Formal Pancreatic Resections and Parenchyma-Sparing Resections for Small PanNETs (<2 cm): Pancreas2000 Research and Educational Program (Course 9) Study Protocol - Pea, Antonio; Tanno, Lulu; Nykänen, Taina; Prasad, Pooja; Tunçer, Ceren; Robinson, Stuart; Marchegiani, Giovanni (Frontiers in Medicine, 2020)
Pancreatic neuroendocrine tumours (PanNETs) are rare tumours but incidence is increasing. An increasing number of these tumours are diagnosed incidentally when they are small (<2cm) and when patients are asymptomatic. The European Neuroendocrine Tumour Society (ENETS) recommends conservative watch and wait policy for these patients. However, the best surgical approach in managing these small tumours in cases where the tumour increases in size beyond 2cm but is still small or when the patient wishes the tumour to be removed is yet unclear. Parenchyma-sparing resections such as enucleation is associated with higher risk of post-operative morbidity compared to formal oncological resections. They are also be associated with potentially inadequate surgical margin clearance and with lack of lymphadenectomy for full pathological staging. Method: This study is a retrospective study and the aim is to analyse pre-operative clinical predictors of nodal metastases for small PanNETs to identify which patients are at a lower risk of lymph node metastases and are therefore suitable for parenchyma-sparing resection. Conclusion: The primary endpoint of this study is to determine if pre-operative clinical predictors such as tumour size are associated with lymph node involvement in small PanNETs. Integrated Research Application System No. (UK): 269312